Assessing the potential economic benefits and environmental impacts of extracting shale gas in the Karoo, South Africa - Bezuidenhout, André (My University, 2018)
The decision to tap into the shale gas resources of the Karoo region in South Africa has become a topic of serious debate. Proponents highlight the significant potential economic gains and contribution to the energy mix. Adversely, there is great concern over the environmental risks involved, most importantly, the use and contamination of precious water resources. However, to not explore the opportunity any further due to environmental concerns is a decision that should be considered deeply. An early stage exploration programme, that does not include any fracking, could be of great benefit to understand the exact extent of the resource. If determined uneconomical, there is no longer a debate. However, if proven significant, a focus on the environmental risks will help assess the exact extent of the impact. Provided this new information, a more accurate cost-benefit analyses will be required to determine if fracking the Karoo will be worth it. Fracking, South Africa, Karoo, economic benefits, economic costs, environmental risks.
A research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2018